2009
DOI: 10.1103/physrevb.79.233406
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical calculation for the ultraviolet optical properties of single-walled carbon nanotubes

Abstract: We present a theoretical study of the ultraviolet ͑UV͒ optical properties of carbon nanotubes based on the local-density approximation in density functional theory and the generalized tight-binding approximation. Our calculations indicate that the absorption spectrum in the UV region depends strongly not only on nanotube diameter but also on chiral index. In zigzag nanotubes with even indices, peculiar features in the UV absorption spectrum emerge. In sharp contrast, these features are absent from the spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…In contrast to the energydependent optical absorption of graphene 48 , C nr abs;C here remains comparable to the ideal (that is, related to the fine structure constant a ¼ e 2 /(4pe 0 :c)) graphene absorbance, A ¼ C abs,C / pa 2 C ¼ pa, in the 1.5-3.0 eV spectral range, suggesting different influences of interband transitions on CNT absorption 50 .…”
Section: Discussionmentioning
confidence: 85%
“…In contrast to the energydependent optical absorption of graphene 48 , C nr abs;C here remains comparable to the ideal (that is, related to the fine structure constant a ¼ e 2 /(4pe 0 :c)) graphene absorbance, A ¼ C abs,C / pa 2 C ¼ pa, in the 1.5-3.0 eV spectral range, suggesting different influences of interband transitions on CNT absorption 50 .…”
Section: Discussionmentioning
confidence: 85%
“…The spectral features in the NUV energy region are characteristic of inter-band transitions near the M point of the hexagonal BZ of graphene. 36,38 In this energy range, by dividing them into odd and even tubes (m are odd or even), we observed that they have two distinct peaks, independent of their chirality and radius. By increasing the nanotube diameter, the difference in their energy positions decreased and their peak intensities increased.…”
Section: Optical Propertiesmentioning
confidence: 94%
“…First, there is strong dependence on radius and chirality in the infrared region and, second, odd-even index dependence in the NUV energy region in contrast to the infrared. 36,38 To clarify these results, we investigated the dependence of the energy ratio between the second and first optical transitions (E 22 /E 11 ) in term of radius and chiral angle which are shown in Fig. 8.…”
Section: Optical Propertiesmentioning
confidence: 96%
“…Despite the fact that these spectroscopic signatures can, in theory, be conveniently probed using conventional analytical techniques, specifically the use of UV-vis spectroscopy to assess the p plasmon absorbance, few examples exist in the scientific literature and to date and the best of our knowledge there are no systematic studies which look to correlate the morphological and structural characteristics of the bulk nanotube sample with the position and intensity of the p plasmon absorbance. Furthermore, advanced techniques, such as electron energy loss spectroscopy (EELS) and a variety of theoretical approaches have yielded somewhat ambiguous and contradictory results in recent times [13][14][15][16][17][18][19][20][21][22][23]. In this communication, we report for the first time a comprehensive study of the p plasmon absorbance of a series of SWNT using ultraviolet-visible (UV-vis) spectroscopy.…”
Section: Introductionmentioning
confidence: 98%